2000
DOI: 10.1042/0264-6021:3450239
|View full text |Cite
|
Sign up to set email alerts
|

Efficient solubilization and purification of the gastric H+,K+-ATPase for functional and structural studies

Abstract: When gastric H(+),K(+)-ATPase-containing microsomes are solubilized by detergents, a rapid loss of ATPase activity is generally observed. In this article, SDS/PAGE of octa(ethylene glycol)dodecyl monoether (C(12)E(8))- and n-dodecyl beta-d-maltoside-solubilized microsomes and their purifications by affinity chromatography on Reactive Red column reveal that inactivation is due to two main effects. (i) Solubilization activates an aspartic protease that cleaves down the alpha-subunit of the H(+),K(+)-ATPase. Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…These data can be taken to indicate the existence of a slow equilibrium between oligomers in solution, since more than 2 h is required for the fixation and observation of H/K-ATPase molecules at room temperature. The solubilization of active H/K-ATPase using C 12 E 8 at 5 °C has been reported (15). However, further studies are required to obtain an active solubilized H/K-ATPase with C 12 E 8 at room temperature as in the case of other P-type ATPases (31,42).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These data can be taken to indicate the existence of a slow equilibrium between oligomers in solution, since more than 2 h is required for the fixation and observation of H/K-ATPase molecules at room temperature. The solubilization of active H/K-ATPase using C 12 E 8 at 5 °C has been reported (15). However, further studies are required to obtain an active solubilized H/K-ATPase with C 12 E 8 at room temperature as in the case of other P-type ATPases (31,42).…”
Section: Discussionmentioning
confidence: 99%
“…However, a large body of evidence has accumulated to indicate that the functional native enzyme in the membrane is an oligomer comprised of Rβ-protomers in H/K-ATPase (9)(10)(11)(12)(13)(14)(15)(16)(17) and Na/K-ATPase (16,(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28) or a 2n-mer in sarcoplasmic Ca/H-ATPase (29)(30)(31). In the case of H/K-ATPase, the following data provide strong support for the oligomericity of the enzyme: studies of radiation inactivation (10), stoichiometry of phosphorylation and ATP binding (12) E3810 (rabeprazole) binding (14), chemical cross-linking with copper orthophenanthroline (13), blue-native polyacrylamide electrophoresis (15), a glycerol density gradient of detergent-extracted enzyme (9), and two-dimensional crystals (11). We recently showed that the maximum absolute amount of EP formed from ATP was 0.5 mol/mol of R-chain, which is half the amount of EP obtained from P i or acetyl phosphate (12,17).…”
mentioning
confidence: 99%
“…Surfactants are indispensable reagents in the solubilization and reconstitution of membrane proteins. The need to find effective and predictable means to solubilize and reconstitute these membranes, as well as to devise appropriate protocols for biological research or pharmacological applications is one reason for interest in the study of membrane−surfactant interactions. In this field, one of the most commonly used amphiphilic compounds is the nonionic surfactant octyl glucoside (OG), whose structural properties have been recently studied .…”
Section: Introductionmentioning
confidence: 99%
“…5 ). It is well known that the electro-neutral detergents, DDM, OG and OTG are mild agents for the solubilization of native cell membranes because the lengths of their alkyl chains are all similar, and moreover, almost identical to the hydrophobic chains of lipids 33 , 34 . In contrast, ionic and amphoteric detergents are not mild agents, and lead to a comparably low activity of the proteins.…”
Section: Discussionmentioning
confidence: 99%